Relationship between Bacterial Urinary Tract Infections and Levels of Basic Inflammatory Indicators in Patients with Rheumatoid Arthritis. (World Journal of Experimental Biosciences, 2022)
Rheumatoid arthritis (RA) is considered one of the complex autoimmune diseases that affects not only the body’s joints but can also affect various organs of the body. There are several inflammatory markers such as erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) used to estimate the activity and progression of the disease (RA). The current study aims to highlight the effect of bacterial urinary tract infections (UTIs) on the level of some inflammatory indicators (ESR and CRP), in addition to the level of antinuclear antibodies (ANA) in the peripheral blood of patients with RA. The present study included 70 patients suffering from (RA) divided into two groups, the first group contained 40 patients (24 female and 6 male) with RA and UTI; the second group, 29 patients suffering from RA (24 female and 5 male) without bacterial UTIs, and 30 healthy control cohorts. The study showed that the levels of ESR, CRP, and ANA in the group of patients suffering from RA and bacterial UTI were not statistically different from their levels in patients suffering from RA only (without bacterial UTIs). The bacterial species (UTIS) did not affect the levels of ESR, CRP, and ANA in patients with RA and UTIs. The current study showed that bacterial infection of the urinary tract does not affect the level of basic inflammatory indicators (ESR and CRP) in patients with RA. It also does not affect the level of ANA. The study showed that the age factor and the period of treatment that a patient with RA undergoes do not affect the incidence of bacterial UTIs.